PENGGUNAAN MINYAK CENGKEH DALAM APLIKASI EDIBLE FILM WHEY TERHADAP KARAKTERISTIK KIMIAWI DAN MIKROBIOLOGIS KEJU GOUDA - Fahrullah Fahrullah (Agroindustrial Technology, University of Trunojoyo Madura, 2021)
The research aims to observe whey edible film coating clove oil antimicrobial compounds on the chemical and microbiological characteristics of gouda cheese. The chemical and microbiological characteristics of Gouda cheese covered with whey edible film were investigated using an experimental method. The research was conducted in a completely randomized design with four treatments. The treatment used different concentrations of clove essential oil (0 %; 5 %; 10 % and 15 %). The value of water content, water activity, color (L*,b*), and inhibition against pathogenic microbes gave a significant value (P0.01) with the addition of clove essential oil concentration. The chemical of gouda cheese coated with whey edible film clove essential oil antimicrobial agent showed that water content was at 41.57 - 43.38 %, the water activity was at 0.915 - 0.930, the color (L* was at 59.07-61.50; a* was at 10.57-11.46; b* was at 23.51 - 25.80) and the treatment starting from a concentration of 5 % clove essential oil resulted in high inhibition of pathogenic microbial, molds, and yeasts.